PENANAMKAN NILAI-NILAI PENDIDIKAN ISLAM QS LUQMAN AYAT 12-19 DI SMPN 1 GUDO JOMBANG - Ali Mustofa; Taufiqur Rochman (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2023)
Islamic education is a business that educates, guides, fosters, influences, and directs based on the Al-Quran and As-Sunnah Surah Lukman verses 12-19 discusses the story of Lukman al-Hakim when educating his children about monotheism, worship and morals. QS Lukman verses 12-19 contain the values of Islamic education that must be instilled in children so that they become a way of life. The aims of this study were: (1) to describe the values of Islamic education in QS Luman verses 12-19 (2) to describe the role of PAI teachers in instilling Islamic education values based on QS Luman verses 12-19 to students of SMPN 1 Gudo Jombang. This type of research is a qualitative field research (field research). This study uses a case study research design. Data collection techniques using interview techniques, observation, and documentation. Furthermore, data analysis was carried out using the case study analysis method. The results of the research that the author has conducted show that the Islamic education values of SMPN 1 Gudo students based on QS Luqman verses 12-19 include monotheism values, worship values, and moral values which consist of being grateful, patient, devoted to both parents, and avoiding arrogance. The role of PAI teachers in instilling the values of Islamic education based on QS Luman verses 12-19 to students at SMPN 1 Gudo is to use the habituation method where the habituation method is applied to activities at school such as monotheism learning, midday prayers in congregation, istighosah, dhuha prayers in congregation, routines yasin and tahlil, reading diba and sholawat prophet, commemoration of Eid al-Adha, pondok romadhon, zakat fitrah, reading selected letters before studying, courtesy, greeting teachers and friends when meeting, being kind to parents, speaking soft words, carrying out orders parents, learn about gratitude.